The Emperor's new shroud: international response to CBRN - Johnson, Stephen (CBRNe World, 2016)
Steve Johnson, lecturer on forensic exploitation and intelligence at Cranfield university, wonders whether anyone is coming to help in the event of an international CBRN incident.
Keywords: Forensics; Investigation; Aid; Humanitarian; CBRN